An updated review of the pharmacological effects and potential mechanisms of hederagenin and its derivatives - Zhang, Huize; Li, Yong; Liu, Yi (Frontiers in Pharmacology, 2024)
Hederagenin (HG) is a natural pentacyclic triterpenoid that can be isolated from various medicinal herbs. By modifying the structure of HG, multiple derivatives with superior biological activities and safety profiles have been designed and synthesized. Accumulating evidence has demonstrated that HG and its derivatives display multiple pharmacological activities against cancers, inflammatory diseases, infectious diseases, metabolic diseases, fibrotic diseases, cerebrovascular and neurodegenerative diseases, and depression. Previous studies have confirmed that HG and its derivatives combat cancer by exerting cytotoxicity, inhibiting proliferation, inducing apoptosis, modulating autophagy, and reversing chemotherapy resistance in cancer cells, and the action targets involved mainly include STAT3, Aurora B, KIF7, PI3K/AKT, NF-κB, Nrf2/ARE, Drp1, and P-gp. In addition, HG and its derivatives antagonize inflammation through inhibiting the production and release of pro-inflammatory cytokines and inflammatory mediators by regulating inflammation-related pathways and targets, such as NF-κB, MAPK, JAK2/STAT3, Keap1-Nrf2/HO-1, and LncRNA A33/Axin2/β-catenin. Moreover, antipathogen, anti-metabolic disorder, anti-fibrosis, neuroprotection, and anti-depression mechanisms of HG and its derivatives have been partially elucidated. The diverse pharmacological properties of HG and its derivatives hold significant implications for future research and development of new drugs derived from HG, which can lead to improved effectiveness and safety profiles.